Pengaruh Pembelajaran Aktif Berbantuan Media Wayang Kertas Terhadap Ketrampilan Berbicara Siswa - Fitri Anisa (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the active learning model assisted by paper puppetmedia on the speaking skills of third grade students at Surodadi 3 Candimulyo StateElementary School, Magelang Regency. This study uses a pre-experimental design methodof the type of one group pretest-posttest. The population in this study were all third gradestudents at SDN Surodadi 3 Candimulyo, totaling 17 students. The research subjects wereselected using a saturated sampling technique. The method of data collection is done byusing a performance assessment. The validity test of the performance assessmentinstrument was carried out using expert validity. The analysis prerequisite test consists ofa normality test and a hypothesis test. Data analysis used parametric statistical techniques,namely the paired sample T-Test test with the help of the SPSS version 22 for windowsprogram. The results of data analysis using the paired Sample T-test showed a significancevalue (2-tailed) 0.000 <0.05. Based on the results of data analysis, the average pretest score was 60 while the posttest score was 74. These results showed an increase in the pretest-posttest score of 23%. The results of the study concluded that the use of active learning models assisted by paper puppet media had an effect on students' speaking skills.